2000
DOI: 10.1176/appi.ajp.157.7.1150
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Persistent Tardive Dyskinesia in Elderly Patients With Dementia Treated With Risperidone

Abstract: Although there was no control group, the observed incidence of persistent tardive dyskinesia with risperidone seemed to be much lower than that seen in elderly patients treated with conventional neuroleptics. The average optimal dose of risperidone in elderly dementia patients was found to be 0.75-1.5 mg/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(74 citation statements)
references
References 24 publications
1
72
0
1
Order By: Relevance
“…An atypical antipsychotic agent is usually selected on the basis of a patient's clinical profile and in consideration of the agent's efficacy data and specific adverse-effect profile. The positive effects of risperidone and olanzapine on TD symptoms have been reported in clinical trials (1,2,13,14,33,63) and in case studies ( Table 4). Chouinard reported an antidyskinetic effect of risperidone in the multicentre Canadian trial (63).…”
Section: Switching From Conventional To Atypical Antipsychoticsmentioning
confidence: 81%
See 1 more Smart Citation
“…An atypical antipsychotic agent is usually selected on the basis of a patient's clinical profile and in consideration of the agent's efficacy data and specific adverse-effect profile. The positive effects of risperidone and olanzapine on TD symptoms have been reported in clinical trials (1,2,13,14,33,63) and in case studies ( Table 4). Chouinard reported an antidyskinetic effect of risperidone in the multicentre Canadian trial (63).…”
Section: Switching From Conventional To Atypical Antipsychoticsmentioning
confidence: 81%
“…Although the elderly have an increased risk for TD associated with conventional antipsychotic treatment, low rates of movement disorders and TD have been reported in several trials of risperidone in elderly patients with psychosis or dementia (1,2,(29)(30)(31)(32)(33)(34). Davidson and colleagues studied 180 elderly, chronically ill patients with psychosis who received risperidone at a mean dosage of 3.7 mg daily for up to 1 year (31).…”
Section: Atypical Antipsychotics and Tdmentioning
confidence: 99%
“…Although we found no evidence for an effect of dose on TD risk in this study where doses were very low, resulting in comparable EPS rates for these two SGAs, it is possible that differences between the drugs might emerge at higher dose levels when one would also expect to see a greater differentiation in EPS liability. This is suggested by results from one study in the elderly where there was a dose-dependent TD risk (Jeste et al, 2000). It must be emphasized that interpretation of the comparisons between the TD rates for the two antipsychotics is constrained by the sample size and the fact that the drugs were not randomly assigned.…”
Section: Discussionmentioning
confidence: 99%
“…In the elderly, annualized TD incidence rates for SGAs ranged from 2.5% (olanzapine (Kinon et al, 2005) and risperidone (Jeste et al, 2000)) and 2.7% (quetiapine; Glazer et al, 1999) in patients with exclusive or predominant dementia, to 13.6% with risperidone (Davidson et al, 2000) in patients with mostly chronic schizophrenia, receiving high-dose risperidone, which exerted a dose effect on TD. In the 2004 review (Correll et al, 2004), no concurrent FGA TD rates in the elderly had been available.…”
Section: Introductionmentioning
confidence: 99%
“…Risperidone, an antipsychotic drug that presents antagonist properties on dopamine D 2 , serotonin 5HT 2 and α 1 adrenoreceptors, has been the focus of several clinical studies [38,39]. The study carried out by Su et al [40], using MK-801 (ketamine-like NMDA antagonist), showed that risperidone had an inhibitory effect on MK-801-induced hyperactivity in mice, at doses in which it caused no alteration in spontaneous activity when administered alone.…”
Section: Discussionmentioning
confidence: 99%